hello there!
to find the turning point, you must have a function, so let's set this expression equal to y.
y=(c-2)^3+8
y'=3(c-2)^2
Now set y' equal to 0...
3(c-2)^2=0
3(c-2)(c-2)=0
c=2
Now that we know c=2, plug this in to the original equation to get the y-value for the turning point.
The turning point is (2,y) we will find y now...
y=(2-2)^3+8
y=0+8
y=8
The turning point is at (2,8)
The explanation for this is that the x values of the zeros of the derivative function are the same as the x values as the turning points on the original function.
I really hope this helps!
Best wishes :)